Competence Based Assessment of Listening Skill for ESL Students - Dương, Thị Anh (H. : ĐHQGHN, 2017)
Competence based assessment has become a modern and effective way of evaluating leaners’ competencies, especially in English. This paper focuses on demonstrating the effect of competence based assessment to adjust teaching and learning English listening skill for English as a second language (ESL) students. The tools used in this research are test items which are defined to test certain competencies by English experts (teachers). The collected data is then analyzed by special programs of Statistical Package for Social Service (SPSS) and Conquest program. The study results were then confirmed relied on theoretical base and competence framework as Common European Framework of References (CEFR) for foreign languages